Elucidating the photovoltaic effect of monoclinic K2SnBr6 by mixed-cation mixed-halide substitution from first-principles calculations. (29th December 2022) - Sreedevi, P D; Ravindran, P
Abstract: Vacancy-ordered double perovskites (A2 BX6 ) have recently received impressive attention for photovoltaic applications, and the compound K2 SnBr6 has desirable features for use in solar cells in such a way that it exhibits direct bandgap behaviour with dispersed band edges. However, the large bandgap value limits its use in higher-efficiency solar cells. Therefore, we have carried out exploratory research by analysing the photovoltaic effect of K2 SnBr6 by tuning its bandgap with cation and anion substitutions. We studied the properties of K(2− y ) Rby SnBr(6− x ) I x and K2 Sn(1− z ) Ti z Br(6− x ) I x compounds to explore the photovoltaic effect by gradual substitution of Rb +, Ti 4+ and I −1 for K +, Sn 4+ and Br −1, respectively. Our density functional calculations in the monoclinic ground state crystal structure with the space group P 121 /n revealed that the K(2− y ) Rb y SnBr(6− x ) I x compounds considered in this study exhibit direct bandgap behaviour with well-dispersed band edges. Moreover, the bandgap value decreases as a function of the Rb and I concentrations. In addition to the low charge carrier effective mass, low excitonic binding energy values and low recombination rate, these compounds exhibit comparatively greater absorption coefficients in the visible range. The charge carrier transport properties, such as carrier mobility, carrier relaxation time, carrier diffusion coefficient and carrier diffusion length, are also seen in higher ranges for these Rb- and I-substituted compounds when compared to the parent compound. In addition, we have calculated the open-circuit voltage, fill factor, short-circuit current and power conversion efficiency for each compound. From the calculations and analysis, we observed that Rb and I substitution in K2 SnBr6 increases the photovoltaic effect, and thus K(2− y ) Rb y SnBr(6− x ) I x compounds may be employed as absorbing layers in higher-efficiency solar cells.